FACTORS AND DIRECTIONS OF FOREIGN INVESTMENTS ATTRACTION INTO TIMBER PROCESSING COMPLEX OF THE RUSSIAN FEDERATION - F. Chomaev (Вестник университета)
The object of research in this article is assessment of a role of the foreign capital in development of timber processing complex of Russia. A main author's objective is identification of opportunities of investment providing forest industry at the present stage. The analysis has shown that structural imbalances in Russia' forest industry shows the problems of its effective investment providing and financing that, in particular, is caused by deficiency of foreign capital investments. In the Russian timber processing complex influence of the foreign capital is considered not only from the point of view of financing, but also as a factor of attraction of technologies, experience of management. In the article major factors of realization of investment potential of forest industry from the point of view of attraction of the foreign capital are considered.